Quantum mechanics-based scoring rationalizes the irreversible inactivation of parasitic Schistosoma mansoni cysteine peptidase by vinyl sulfone inhibitors - Fanfrlík, Jindřich; Brahmkshatriya, Pathik S; Řezáč, Jan; Jílková, Adéla; Horn, Martin; Mareš, Michael; Hobza, Pavel; Lepšík, Martin (The journal of physical chemistry. B, 2013)
The quantum mechanics (QM)-based scoring function that we previously developed for the description of noncovalent binding in protein-ligand complexes has been modified and extended to treat covalent binding of inhibitory ligands. The enhancements are (i) the description of the covalent bond breakage and formation using hybrid QM/semiempirical QM (QM/SQM) restrained optimizations and (ii) the addition of the new ΔG(cov)' term to the noncovalent score, describing the "free" energy difference between the covalent and noncovalent complexes. This enhanced QM-based scoring function is applied to a series of 20 vinyl sulfone-based inhibitory compounds inactivating the cysteine peptidase cathepsin B1 of the Schistosoma mansoni parasite (SmCB1). The available X-ray structure of the SmCB1 in complex with a potent vinyl sulfone inhibitor K11017 is used as a template to build the other covalently bound complexes and to model the derived noncovalent complexes. We present the correlation of the covalent score and its constituents with the experimental binding data. Four outliers are identified. They contain bulky R1' substituents structurally divergent from the template, which might induce larger protein rearrangements than could be accurately modeled. In summary, we propose a new computational approach and an optimal protocol for the rapid evaluation and prospective design of covalent inhibitors with a conserved binding mode.
Keywords: Animals; vztah mezi dávkou a účinkem léčiva; Quantum Theory; Molecular Structure; Structure-Activity Relationship; sulfony; Vinyl Compounds; Sulfones; krystalografie rentgenová; cysteinové proteasy; Models, Molecular; molekulární struktura; Cysteine Proteinase Inhibitors; Dose-Response Relationship, Drug; molekulární modely; Cysteine Proteases; vztahy mezi strukturou a aktivitou; zvířata; Crystallography, X-Ray; inhibitory cysteinových proteinas; kvantová teorie; Schistosoma mansoni; vinylové sloučeniny